Steps per day among persons with multiple sclerosis: variation by demographic, clinical, and device characteristics - Dlugonski, Deirdre; Pilutti, Lara A; Sandroff, Brian M; Suh, Yoojin; Balantrapu, Swathi; Motl, Robert W (Archives of physical medicine and rehabilitation, 2013)
To identify steps per day in a large sample of persons with multiple sclerosis (MS) and to describe variation by demographic and clinical characteristics and device type. Cross-sectional design. General community. Convenience sample of persons with multiple sclerosis (N=645) recruited from the general community who were ambulatory and relapse free for 30 days. Mean age ± SD of the participants was 46.3 ± 10.6 years old. Participants were mostly women (85%), white (93%), and employed (64%). Not applicable. Step counts measured by a motion sensor during a 7-day period. The average value for the entire sample was 5,903 ± 3,185 steps per day. This value varied by demographic and clinical characteristics, but not device type, and indicated that men, participants who were unemployed, had a high school education or less, progressive MS, a longer disease duration, and higher disability were less physically active based on the metric of steps per day. This study provides an expected value for average steps per day among persons with MS. Such an expected value for this population is an important first step to help researchers and clinicians interested in improving the overall health of persons with MS through physical activity promotion.